Equity, Equality and the Social Bond Theory In Schools: A Heads Up for Teacher Educators - Stu Ervay (The Advocate, 2016)
Today’s schools face challenges that go beyond those of the 20th Century, in addition to the more recent impact of No Child Left Behind. Common core standards and stipulations found in the recent Every Student Succeeds Act (ESSA) call for new academic programs and ways for teachers to implement them. Integral to the ESSA are techniques for achieving social equity, equality of learning opportunity, and “wrap-around support systems for vulnerable communities.” The community support systems concept can include what sociologists call the social bond theory. For schools and teachers to make those goals achievable within classrooms will require more emphasis on project-based teaching and learning.